Bacterial Burden Declines But Neutrophil Infiltration and Ocular Tissue Damage Persist in Experimental Staphylococcus epidermidis Endophthalmitis - Das, Susmita; Singh, Sukhvinder; Kumar, Ashok (Frontiers in Cellular and Infection Microbiology, 2021)
Coagulase-negative staphylococci (CoNS), including Staphylococcus (S) epidermidis are responsible for 70% of all post-surgical endophthalmitis, a potentially blinding eye infection. However, the pathobiology of CoNS endophthalmitis is limited to epidemiological and clinical case studies with few experimental studies. Here, we report both in vitro and in vivo models to study the pathobiology of S. epidermidis endophthalmitis in mice. We found that S. epidermidis is rapidly cleared from mouse eyes and a relatively higher dose (i.e., 107 CFU/eye) was needed to cause endophthalmitis. Our time-course study revealed that bacterial load peaked at 24h post-infection followed by a gradual decline up to 72h. A similar time-dependent decrease in levels of inflammatory mediators and Toll-like receptors (TLRs) expression was also observed. In contrast, neutrophil infiltration continued to increase up to 72h coinciding with significant retinal tissue damage and loss of visual function. In vitro, S. epidermidis induced the activation of various inflammatory signaling pathways (i.e., NF-kB, ERK and P38) and the production of both cytokines and chemokines in mouse BMDMs, human RPE and retinal Muller glia. Altogether, we show that bacterial burden is reduced in S. epidermidis endophthalmitis while tissue damage and visual function loss continues. Thus, our study provides new insights into the pathogenesis of CoNS endophthalmitis.